2022
DOI: 10.1002/jum.16120
|View full text |Cite
|
Sign up to set email alerts
|

The Course and Neonatal Outcome of Choroid Plexus Extension to the Anterior Horn at the Routine Anatomy Scan

Abstract: Objectives Our objective was to examine the pregnancy course and immediate neonatal outcome of fetuses with an isolated extension of choroid plexus (CP) to the anterior horn during the second trimester. Methods We prospectively collected the cases referred to us between July 2012 and January 2021 with isolated finding of CP extension to the anterior horn. Relevant clinical and demographic information was recorded, and a full anatomy scan including a comprehensive neurosonogram was performed. In cases of confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In our study, we showed that by 14–16 weeks, the CP in one or both hemispheres may still reach the level of the foramen of Monro or extend anteriorly to it, before subsequently moving toward its final posterior location. Additionally, it has been shown that later persistent anterior extension of the choroid plexus (CP) may be seen later in pregnancy, usually representing a benign finding, with a concomitant presence of a CPC in the anterior horn in 38% of cases 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we showed that by 14–16 weeks, the CP in one or both hemispheres may still reach the level of the foramen of Monro or extend anteriorly to it, before subsequently moving toward its final posterior location. Additionally, it has been shown that later persistent anterior extension of the choroid plexus (CP) may be seen later in pregnancy, usually representing a benign finding, with a concomitant presence of a CPC in the anterior horn in 38% of cases 24 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown that later persistent anterior extension of the choroid plexus (CP) may be seen later in pregnancy, usually representing a benign finding, with a concomitant presence of a CPC in the anterior horn in 38% of cases. 24 The process of neuronal proliferation and migration results in a transient lamination pattern of the cerebral wall. 2,3 Postmortem histologic studies, 2,25 has identified seven distinct layers at 17 weeks.…”
Section: Discussionmentioning
confidence: 99%